Online Surveillance in a Swedish Context: Between acceptance and resistance - Cocq Coppélie; Gelfgren Stefan; Samuelsson Lars; Enbom Jesper (Nordicom Review, 2020)
Users of digital media leave traces that corporations and authorities can harvest, systematise, and analyse; on the societal level, an overall result is the emergence of a surveillance culture. In this study, we examine how people handle the dilemma of leaving digital footprints: what they say they do to protect their privacy and what could legitimise the collection and storing of their data. Through a survey of almost 1,000 students at Umeå University in Sweden, we find that most respondents know that their data are used and choose to adjust their own behaviour rather than adopting technical solutions. In order to understand contemporary forms of surveillance, we call for a humanistic approach – an approach where hermeneutic and qualitative methods are central.